Pain-related anxiety, sex, and co-use of alcohol and prescription opioids among adults with chronic low back pain - LaRowe, Lisa R.; Powers, Jessica M.; Garey, Lorra; Rogers, Andrew H.; Zvolensky, Michael J.; Ditre, Joseph W. (Drug and alcohol dependence, 2020)
•Pain-related anxiety was positively associated with alcohol and opioid use/misuse.•Pain-related anxiety was positively associated with co-use of alcohol and opioids.•Future work should continue to investigate sex differences in these associations.•Pain-related anxiety may be a transdiagnostic factor underlying alcohol-opioid use. Both alcohol and prescription opioid use/misuse are highly prevalent among individuals with chronic pain. Co-use of alcohol and prescription opioids is also common, despite contraindications due to increased risk of negative health effects and mortality. There is evidence that pain-related anxiety (i.e., the tendency to respond to pain with anxiety or fear) may be associated with heavier drinking and prescription opioid use/co-use, and that these associations may be especially salient among men. This study is the first examination of pain-related anxiety in relation to hazardous alcohol use, prescription opioid use/misuse, and alcohol-opioid co-use. Participants included 1812 adults with chronic low back pain (69 % female, Mage = 43.95) who completed an online survey assessing health behaviors. Pain-related anxiety was positively associated with indices of alcohol (i.e., alcohol-related consequences) and opioid use (i.e., prescription opioid use/misuse, daily opioid consumption). Of note, sex moderated associations between pain-related anxiety and both alcohol-related consequences and prescription opioid misuse. In addition to being associated with alcohol and prescription opioid use, independently, pain-related anxiety was also associated with greater likelihood of endorsing co-use of alcohol and opioids and engaging in concurrent hazardous drinking and prescription opioid misuse. These findings contribute to a growing literature suggesting that pain-related anxiety is an important transdiagnostic factor in pain and alcohol and prescription opioid use/co-use, perhaps especially among males.